Cysteamine-supplemented diet for cashmere goats: A potential strategy to inhibit rumen biohydrogenation and enhance plasma antioxidant capacity - Wu, Tiecheng; Liang, Jianyong; Wang, Tao; Zhao, Ruoyang; Ma, Yuejun; Gao, Yulin; Zhao, Shengguo; Chen, Guoshun; Liu, Bin (Frontiers in Veterinary Science, 2022)
Cysteamine (CS), as a feed supplement, can increase the level of growth hormone (GH) in the blood, promote animal growth. However, little attention has been paid to the effects of CS on the rumen microbiome and metabolic profile in cashmere goats. This study aimed to assess the effects of rumen microbiota, metabolites, and plasma antioxidative capacity induced by CS supplementation in cashmere goats. We selected 30 Inner Mongolia white cashmere goat ewes (aged 18 months), and randomly separate the goats into three groups (n = 10 per group) to experiment for 40 days. Oral 0 (control group, CON), 60 (low CS, LCS), or 120 mg/kg BW−1 (high CS, HCS) coated CS hydrochloride every day. Using 16S and internal transcribed spacer (ITS) rRNA gene amplicon sequencing, we identified 12 bacterial and 3 fungal genera with significant changes among the groups, respectively. We found a significant increase in rumen NH3-N and total volatile fatty acid (TVFA) concentrations in the LCS and HCS groups compared with the CON. With untargeted LC–MS/MS metabolomics, we screened 59 rumen differential metabolites. Among the screened metabolites, many unsaturated and saturated fatty acids increased and decreased with CS treatment, respectively. CS supplementation increased the levels of plasma total antioxidant capacity (T-AOC), glutathione peroxidase (GSH-Px), superoxide dismutase (SOD), GH, and insulin-like growth factor-1(IGF-1). Spearman correlation analysis revealed that the abundance of U29-B03, Lactococcus, and Brochothrix were positively associated with the levels of δ2-THA, TVFA and antioxidant capacity. In conclusion, CS significantly affected rumen microbiota and fermentation parameters, and ultimately inhibited the biohydrogenation of rumen metabolites, enhanced plasma antioxidant capacity, and regulated some hormones of the GH–IGF-1 axis. This study provides an overall view into the CS application as a strategy to improve health production in cashmere goats.